If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+2)(x+3)=24
We move all terms to the left:
(x+2)(x+3)-(24)=0
We multiply parentheses ..
(+x^2+3x+2x+6)-24=0
We get rid of parentheses
x^2+3x+2x+6-24=0
We add all the numbers together, and all the variables
x^2+5x-18=0
a = 1; b = 5; c = -18;
Δ = b2-4ac
Δ = 52-4·1·(-18)
Δ = 97
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-\sqrt{97}}{2*1}=\frac{-5-\sqrt{97}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+\sqrt{97}}{2*1}=\frac{-5+\sqrt{97}}{2} $
| 104+2x+2=180 | | 3x-9=6x-8 | | .43(d)+2=-13 | | 8.8x-1.79=11.41 | | ¼(x+2)=8 | | .75x=225+x | | 12x=(x+3)(x+3) | | 17x=-185 | | 6=12-2f | | 3a-4/2-2a+5/4+3/2=0 | | 40=n*5 | | 6=12–2f | | -2(x+)=2(x-1) | | 31x-12=30 | | 12x=(x+2)(x+2) | | 4/5(5p–20)+6=10 | | 74=3x+20 | | -4b+7=35 | | 4x2=-6 | | 8x+6x^2=-5x+3x^2 | | .75x=225-x | | 41.8c=133.76 | | C(x)=25x+360 | | 3x2+5x+6+x−1x+2=7x+3x | | 7(x1)=49 | | 13u–3u=10 | | 3(n+3)=24 | | 4x+2x-5=-1 | | 18+1/3k=-8 | | 8x-16=3x | | 6x/4-5=1 | | (3a-4/2)-(2a+5/4)+(3/2)=0 |